2020
DOI: 10.1007/s12665-020-09168-z
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale diagenetic facies heterogeneity controls porosity and permeability pattern in reservoir sandstones

Abstract: The fluvial-aeolian Upper Rotliegend sandstones from the Bebertal outcrop (Flechtingen High, Germany) are the famous reservoir analog for the deeply buried Upper Rotliegend gas reservoirs of the Southern Permian Basin. While most diagenetic and reservoir quality investigations are conducted on a meter scale, there is an emerging consensus that significant reservoir heterogeneity is inherited from diagenetic complexity at smaller scales. In this study, we utilize information about diagenetic products and proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 35 publications
1
14
0
2
Order By: Relevance
“…Thus, a burial diagenetic origin of quartz cements based on textural relations is favored. Although it contradicts other interpretations in the same study area (Fischer et al 2012;Heidsiek et al 2020), it is in accordance with observed petrographic textures from different outcrops (Figs. 1c,6g).…”
Section: Quartz Cementssupporting
confidence: 76%
See 1 more Smart Citation
“…Thus, a burial diagenetic origin of quartz cements based on textural relations is favored. Although it contradicts other interpretations in the same study area (Fischer et al 2012;Heidsiek et al 2020), it is in accordance with observed petrographic textures from different outcrops (Figs. 1c,6g).…”
Section: Quartz Cementssupporting
confidence: 76%
“…This study comprises of fluvio-eolian sandstones only, consequently a population bias against a strong control depositional control due to the lack of depositional system variety is introduced into the data set. As opposed to Heidsiek et al (2020) a facies dependent reservoir control on plug-scale reservoir quality analyses cannot be delineated in Flechtingen Sandstones, as is also supported by previous studies in similar arid or semi-arid fluvio-eolian deposits (Busch et al 2019(Busch et al , 2020Kunkel et al 2018;Monsees et al 2020a). The effect of grain size on permeability is also interpreted to be partly caused by a population bias, which is also discussed by Wadsworth et al (2016).…”
Section: Depositional Parametersmentioning
confidence: 55%
“…In this section, the algorithm introduced above is applied to gray-level images of two natural fractures, namely a tensile and a shear fracture. The analyzed tensile fracture is a bedding-parallel joint in a carbonate-cemented aeolian sandstone, which opened up within a block specimen sampled from the Schwentesius outcrop in northern Germany (Fischer et al 2007;Heidsiek et al 2020). Since it can be described as an openingmode fracture, the surface was not exposed to shear stress.…”
Section: Application To Natural Fracture Surfacesmentioning
confidence: 99%
“…In this study, a well-characterized illite-bearing Upper Rotliegend sandstone from Germany was used, which was sampled from the quarry Schwentesius near the Bebertal village (Heidsiek et al 2020). This well-known location exposes an analogue of the Permian gas reservoir sandstone of the Flechtingen High, which formed part of the North German Basin.…”
Section: Sample Preparation and Characterizationmentioning
confidence: 99%